The Evolution of Top Incomes in Switzerland over the 20th Century - Christoph A. Schaltegger; Christoph Gorgas (Swiss Journal of Economics and Statistics, 2011)
We study the income concentration in the Swiss federation over the course of the 20th century using federal income tax statistics. The results suggest that top incomes in Switzerland evolved over time rather remaining constant across different income shares. Income concentration peaked during the 1940s, with a slight downward trend until the 1990s. Over the last 15 years, top incomes have recovered. In contrast, the evolution of income concentration is much more heterogeneous on the sub-federal level for the 26 cantons because of the federalist constitution, which has a decentralized taxing power. Consequently, top incomes in some cantons have a downward trend; others show a fall and rise of top incomes over the century, as exemplified by the Kuznets' hypothesis; some develop rather constantly; and some cantons even produce a striking upward trend.
Keywords: D31; H2; N3; 330; Income inequality; Top incomes; Taxation